Photosensitized [2+2]‐Cycloadditions of Alkenylboronates and Alkenes. Issue 25 (21st April 2022) - Liu, Yanyao; Ni, Dongshun; Stevenson, Bernard G.; Tripathy, Vikrant; Braley, Sarah E.; Raghavachari, Krishnan; Swierk, John R.; Brown, M. Kevin
Abstract: A new strategy for the synthesis of highly versatile cyclobutylboronates via the photosensitized [2+2]‐cycloaddition of alkenylboronates and alkenes is presented. The process is mechanistically different from other processes in that energy transfer occurs with the alkenylboronate as opposed to the other alkene. This strategy allows for the synthesis of an array of diverse cyclobutylboronates. The conversion of these adducts to other compounds as well as their utility in the synthesis of melicodenine C is demonstrated. Abstract : A process for the synthesis of cyclobutylboronates by [2+2]‐cycloaddition is presented. The reaction is enabled by triplet energy transfer to an alkenylboronate, which is an underexplored photochemical process. The process operates with a wide array of alkenylboronates and alkenes to generate a diverse range of products. The utility of the products is demonstrated in the synthesis of melicodenine C.